The Students’ Satisfaction of Online Learning Services - Sofyan Rofi; Bahar Agus Setiawan; Tri Endang Jatmikowati (Program Pascasarjana Universitas Ibrahimy, 2021)
The online learning era found significant momentum when the coronavirus was spreading globally. Innovation, creativity and online learning tools increased significantly and rapidly. All levels of education, from early childhood to university, were racing to provide online learning. This context made the satisfaction dimension of necessity that must be realized by schools/educational institutions. Measurement of satisfaction in learning services was related to five dimensions including reliability, responsiveness, assurance, empathy and tangible. This study aimed to look at the level of satisfaction and the factors that contribute to satisfaction of online learning during the covid-19 pandemic. This study used a qualitative approach with a survey research type based on quantitative descriptive data analysis. The results showed that the average level of satisfaction reached 75%. While, the contributing factors were methods and strategies, and also the discipline and feedback attitudes of the teachers.